Sostenibilidad arquitectónica aplicada a la preservación del patrimonio documental en el municipio de Palmira, Valle del Cauca. - Zuleta López, Natalia; Bermudez Loaiza, Jefersson (Universidad Antonio Nariño, 2021)
The present research aims to give cultural value to the documentary heritage of the municipality of Palmira, Valle del Cauca, based on its preservation through sustainable design criteria to protect its preservation, implementing strategies such as the conservation of physical documents, digitalization, dissemination and accessibility universal and permanent.